Community-based management of Glacial Lake outburst flood : a case study of Samdingkha village in Bhutan - Gyeltshen, Thinlay (BRAC University, 2013)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Disaster Management, 2012.